Natural History of Cardiomyopathy in Adult Dogs With Golden Retriever Muscular Dystrophy. Issue 16 (20th August 2019) - Guo, Lee‐Jae; Soslow, Jonathan H.; Bettis, Amanda K.; Nghiem, Peter P.; Cummings, Kevin J.; Lenox, Mark W.; Miller, Matthew W.; Kornegay, Joe N.; Spurney, Christopher F.
Abstract : Background: Duchenne muscular dystrophy (DMD) is an X‐linked disease that causes progressive muscle weakness. Affected boys typically die from respiratory or cardiac failure. Golden retriever muscular dystrophy (GRMD) is genetically homologous with DMD and causes analogous skeletal and cardiac muscle disease. Previous studies have detailed features of GRMD cardiomyopathy in mostly young dogs. Cardiac disease is not well characterized in adult GRMD dogs, and cardiac magnetic resonance (CMR) imaging studies have not been completed. Methods and Results: We evaluated echocardiography and CMR in 24 adult GRMD dogs at different ages. Left ventricular systolic and diastolic functions, wall thickness, and myocardial strain were assessed with echocardiography. Features evaluated with CMR included left ventricular function, chamber size, myocardial mass, and late gadolinium enhancement. Our results largely paralleled those of DMD cardiomyopathy. Ejection fraction and fractional shortening correlated well with age, with systolic dysfunction occurring at ≈30 to 45 months. Circumferential strain was more sensitive than ejection fraction in early disease detection. Evidence of left ventricular chamber dilatation provided proof of dilated cardiomyopathy. Late gadolinium enhancement imaging showed DMD‐like left ventricular lateral wall lesions and earlier involvement of the anterior septum. Multiple functional indexes were graded objectively and added, with and without late gadolinium enhancement, to give cardiac and cardiomyopathy scores of disease severity. Consistent with DMD, there was parallel skeletal muscle involvement, as tibiotarsal joint flexion torque declined in tandem with cardiac function. Conclusions: This study established parallels of progressive cardiomyopathy between dystrophic dogs and boys, further validating GRMD as a model of DMD cardiac disease.